Study of Organic Acid Corrosion for Steel Pipeline in Wet - Nurulzahar, Farhan Adib (IRC, 2021)
This research aims to study the effect of organic acid corrosion for steel pipeline subjected to top-of-line corrosion (TLC) in wet